DESIGN OF REDUCED-ORDER u-CONTROLLER FOR FLEXIBLE STRUCTURES - Roberd Saragih et al. (Proceedings of ICMSA, 2005)
In this paper, u-controller based on a structured singular value is usedto reduce the vibration of the flexible structures having the transverseand torsion vibrations. Meanwhile, in designing conffol system usingu -controller yields a controller with the order at least equal to the plantorder. Such controller often can not be used in practical application, thusthe order of controller is reduced by using the weighting balancedrealization.Keywords: u-controller; flexible structures, weighting balancedrealization.